Extremely robust femtosecond written fiber Bragg gratings for an ytterbium-doped fiber oscillator with 5 kW output power - Kraemer, Ria G.; Moeller, Friedrich; Matzdorf, Christian; Goebel, Thorsten A.; Strecker, Maximilian; Heck, Maximilian; Richter, Daniel; Ploetner, Marco; Schreiber, Thomas; Tuennermann, Andreas; Nolte, Stefan (Optics Letters, 2020)
We present highly robust fiber Bragg gratings (FBGs) in passive large-mode-area fibers for kilowatt fiber laser systems. The gratings were inscribed directly through the fiber coating using near-infrared femtosecond laser pulses and then implemented in an all-fiber ytterbium-doped single-mode oscillator setup reaching up to 5 kW signal output power. The untreated cooled FBGs showed thermal coefficients as low as 1 K kW−1, proving excellent qualification for the implementation into robust high-power fiber laser setups.
CRIS-Team Scopus Importer:2023-04-20